Principal transformational leadership, self-efficacy, and OCB on teachers innovative work behavior - Afifah Rahmani; Aslamiah Aslamiah; Ngadimun Ngadimun (Universitas Pendidikan Indonesia, 2025)
Innovative work behavior among teachers is crucial for improving educational quality. Teachers are required to create and implement new ideas in the learning process. This innovation encompasses idea exploration, solution development, concept promotion, and actual implementation in the classroom. However, the level of teacher innovation in Indonesia is still relatively low. This study aims to analyze the influence of principals' transformational leadership and teachers' self-efficacy on teachers' innovative work behavior, both directly and indirectly. Using a quantitative approach with descriptive correlational methods and path analysis. A sample of 220 public junior high school teachers in Banjarbaru City was selected using Simple Proportionate Random Sampling technique. Data were collected through closed questionnaires using a Likert scale and analyzed using SPSS version 25. The results show that transformational leadership and self-efficacy have positive and significant effects on OCB and teachers' innovative work behavior. These findings confirm that teacher innovation is influenced by the interaction between individual factors and work environment. The implications of this study highlight the importance of transformational leadership training for principals and strengthening teachers' self-efficacy through professional development. Abstrak Perilaku kerja inovatif guru penting dalam peningkatan mutu Pendidikan. Guru dituntut untuk menciptakan dan menerapkan ide-ide baru dalam proses pembelajaran. Inovasi ini mencakup eksplorasi ide, pengembangan solusi, promosi gagasan, hingga implementasi nyata di kelas. Namun, tingkat inovasi guru di Indonesia masih tergolong rendah. Penelitian ini bertujuan untuk menganalisis pengaruh kepemimpinan transformasional kepala sekolah dan efikasi diri guru terhadap perilaku kerja inovatif guru, baik secara langsung maupun tidak langsung. Menggunakan pendekatan kuantitatif dengan metode deskriptif korelasional dan analisis jalur. Sampel sebanyak 220 guru SMP Negeri di Kota Banjarbaru dipilih menggunakan teknik Simple Proportionate Random Sampling. Data dikumpulkan melalui kuesioner tertutup berskala Likert dan dianalisis menggunakan SPSS versi 25. Hasil menunjukkan bahwa kepemimpinan transformasional dan efikasi diri berpengaruh positif dan signifikan terhadap OCB dan perilaku kerja inovatif guru. Temuan ini menegaskan bahwa inovasi guru dipengaruhi oleh interaksi antara faktor individu dan lingkungan kerja. Implikasi dari penelitian ini adalah pentingnya pelatihan kepemimpinan transformasional bagi kepala sekolah dan penguatan efikasi diri guru melalui pengembangan profesional. Kata Kunci: efikasi diri; kepemimpinan transformasional; OCB; perilaku kerja inovatif